Ultrasound determination of rotator cuff tear repairability. Issue 1 (January 2016) - Tse, Andrew K; Lam, Patrick H; Walton, Judie R; Hackett, Lisa; Murrell, George AC
Background: Rotator cuff repair aims to reattach the torn tendon to the greater tuberosity footprint with suture anchors. The present study aimed to assess the diagnostic accuracy of ultrasound in predicting rotator cuff tear repairability and to assess which sonographic and pre-operative features are strongest in predicting repairability. Methods: The study was a retrospective analysis of measurements made prospectively in a cohort of 373 patients who had ultrasounds of their shoulder and underwent rotator cuff repair. Measurements of rotator cuff tear size and muscle atrophy were made pre-operatively by ultrasound to enable prediction of rotator cuff repairability. Tears were classified following ultrasound as repairable or irreparable, and were correlated with intra-operative repairability. Results: Ultrasound assessment of rotator cuff tear repairability has a sensitivity of 86% ( p  < 0.0001) and a specificity of 67% ( p  < 0.0001). The strongest predictors of rotator cuff repairability were tear size ( p  < 0.001) and age ( p  = 0.004). Sonographic assessments of tear size ≥4 cm 2 or anteroposterior tear length ≥25 mm indicated an irreparable rotator cuff tear. Conclusions: Ultrasound assessment is accurate in predicting rotator cuff tear repairability. Tear size or anteroposterior tear length and age were the best predictors of repairability.